2020
DOI: 10.3332/ecancer.2020.1021
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study to assess the survival outcomes of planned irradiation of ipsilateral subventricular and periventricular zones in glioblastoma

Abstract: Purpose/objective(s): Retrospective evidence suggests that the irradiation of stem cells in the periventricular zone (PVZ), specifically the subventricular zone (SVZ), to higher doses may be associated with improved outcomes. Materials/methods: This was a prospective study, done from 2012 to 2017 in glioblastoma patients to assess the efficacy of planned irradiation of ipsilateral PVZ and SVZ on survival outcomes. The clinical target volume included the tumour bed with a 1.5-2 cm margin, perilesional oedema an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…This is possibly due to the lower vascular supply in these areas as well as to variability in relative biological effectiveness (RBE) when using particle therapy [9][10][11][12]25]. In addition, the innermost region of the PVS, known as subventricular zone, constitutes a major neural stem cells niche and is associated with gliomagenesis [26,27]. Co-registration with T1-weighted MRI is recommended for delineation.…”
Section: Periventricular Space (''Pvs")mentioning
confidence: 99%
“…This is possibly due to the lower vascular supply in these areas as well as to variability in relative biological effectiveness (RBE) when using particle therapy [9][10][11][12]25]. In addition, the innermost region of the PVS, known as subventricular zone, constitutes a major neural stem cells niche and is associated with gliomagenesis [26,27]. Co-registration with T1-weighted MRI is recommended for delineation.…”
Section: Periventricular Space (''Pvs")mentioning
confidence: 99%
“…The first prospective clinical study investigating the irradiation of NSC niches in GBM was conducted on 74 patients who underwent total surgical resection followed by radiotherapy and chemotherapy (33). The CTV included the ipsilateral periventricular zone (PVZ), defined as a 5 mm expansion all around the lateral ventricles, and it included the SVZ, defined as a 5 mm lateral expansion of the lateral ventricles.…”
Section: Review Of the Prospective Studiesmentioning
confidence: 99%
“…reported no correlation between SVZ dose and PFS/OS in multivariate analysis ( 136 ). In a prospective study including 74 GBM patients, the same team did not found any correlation between SVZ dose and PFS/OS ( 137 ). Finally, in a short prospective study of 30 GBM patients, the sparing irradiation of neurogenic niches, including SVZ, did not modify PFS or OS in comparison to a matched historical control ( 139 ).…”
Section: The Subventricular Zone In Clinical Practicementioning
confidence: 99%